IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DALAM PERKULIAHAN MATEMATIKA EKONOMI TERHADAP PEMAHAMAN MAHASISWA - Widya Dwiyanti; Anton Nasrullah (Universitas Sultan Ageng Tirtayasa, 2018)
The level of student ability in solving economic math problems is very less. Though very crucial understanding to learn the application of mathematics in economic problems. The purpose of this research is to know the application of problem-based learning model which is applied in the lecture of economic mathematics to the understanding of student learning. The method used is quasi-experiment pre-test design post-test control group design with data collection using test and attitude questionnaire. Samples were 30 students of experimental class and 31 students of the control class. The findings indicate that problem-based learning (experimental class) is better than the expository (class of control) on understanding in economic mathematics learning. Not only that, students in the experimental group show a positive attitude toward the learning of economic mathematics. The findings of this study have implications for encouraging lecturers learn how to understand environmental mathematics. Keywords: Problem-Based Learning, Understanding, Attitude.